Process limits improvement in sheet injection using locally heat-treated aluminium alloy - Magrinho João P.; Cusanno Angela; Jesus Miguel L.; Piccininni Antonio; Guglielmi Pasquale; Palumbo Gianfranco; Silva M. Beatriz (MATEC Web of Conferences)
The present study investigates the possibility of improving the technological limits of the sheet injection process using locally heat-treated aluminium alloys to address challenges such as underfilling and material flaws. Aluminium alloys are highly valued in lightweight design due to their excellent strength-to-weight ratio, but their limited formability remains an open challenge in advanced manufacturing processes. This work focuses on the design of the laser heating to locally bring an age-hardenable aluminium alloy (AW6082) from the T6 purchasing temper to a full overaged condition to improve its formability in targeted zones. The sheets, characterized by a gradient of properties, are then subjected to injection by upsetting the side walls. The experimental work includes mechanical characterisation by means of tensile and compression tests, as well as sheet injection trials. Numerical simulations are conducted to predict and optimise the material flow during the injection process. Results demonstrate that the localised heat treatment allowed to effectively enhance the formability of aluminium alloys at room temperature, enabling the successful achievement of complex geometries with a reduced risk of defects such as material flaws. Key insights include material flow control in obtaining defect-free sheet-bulk parts. The study offers a comprehensive approach combining the local modification of the material properties with an advanced forming process, paving the way for more efficient production of lightweight and high-performance parts.